2015
DOI: 10.1016/j.rpped.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Indicadores antropométricos para identificar síndrome metabólica e fenótipo cintura hipertrigliceridêmica: uma comparação entre as três fases da adolescência

Abstract: OBJECTIVE: To determine the prevalence of metabolic syndrome (MS) and the hypertriglyceridemic waist phenotype (HW) in a representative adolescent sample; as well as to establish which anthropometric indicator better identifies MS and HW, according to gender and adolescent age. METHODS: This cross sectional study had the participation of 800 adolescents (414 girls) from 10-19 years old. Anthropometric indicators (body mass index, waist perimeter, waist/stature ratio, waist/hip ratio, and central/peripheral ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
0
8
0
4
Order By: Relevance
“…Adolescence is a stage of physical and intellectual changes [2,59] where there is intense body growth that interferes with the accumulation and distribution of body fat [44]. It is therefore seen as one of the most critical periods for the development of obesity [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescence is a stage of physical and intellectual changes [2,59] where there is intense body growth that interferes with the accumulation and distribution of body fat [44]. It is therefore seen as one of the most critical periods for the development of obesity [17].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the anthropometric indicators, waist circumference is already a consolidated index for the analysis of central fat and cardiovascular risk [37,38,39]. In addition, the circumference of the arm, hip, and calf are used to assess the nutritional status and population health [22,23,25,40,41,42,43,44,45,46]. Other factors were considered, such as low cost, reproducibility, and accessibility to the entry attributes, especially if the method is used in remote places.…”
Section: Methodsmentioning
confidence: 99%
“…In a cohort with students from a city in Bahia involving children and adolescents, Costa et al 12 found a prevalence of 10.6%. In studies conducted by Pereira et al 11 and Conceição-Machado et al, 8 the phenotype was prevalent only in adolescents, with 6.4 and 7.2%, respectively. These differences in prevalence can be explained by the different cut-off points adopted to classify WC and TG, and subsequent definition of the HTGW phenotype.…”
Section: Discussionmentioning
confidence: 88%
“…9 In 2000, Lemieux et al developed one of the first studies involving HTGW with a sample of Canadian male adults, finding high agreement between this index and the atherogenic metabolic triad. 10 Nevertheless, despite the lack of studies involving individuals with T1DM nationwide, the literature has presented research with several populations, including children 11 and adolescents, 8,12 indicating a scenario in which CVDs represent the main cause of morbidity and mortality, affecting increasingly younger individuals and significantly reducing productive life. Thus, this study aimed to evaluate the frequency of the HTGW phenotype and its associated factors in children and adolescents with T1DM.…”
Section: Introductionmentioning
confidence: 99%
“…It is conceptualized as a phase of several structural and behavioral transformations, especially in the psychic, physical, biological and social aspects 2 . For statistical data, we can divide it into three stages: initial adolescence (10-13 years), intermediate adolescence (14-16 years) and final adolescence (17)(18)(19) years) 3 .…”
Section: Introductionmentioning
confidence: 99%